The Language of Risk, Public Policies, and Childbirth in the Municipality of São Paulo: A Reading of Data From the Live Birth System 2010–2016 - Brigagão, Jacqueline I. M.; Gonçalves, Roselane; Nascimento, Vanda L. V. D. (Frontiers in Sociology, 2018)
The main factor for the hospitalization of childbirth was the expansion of power-knowledge in 18th century medicine. In Brazil, throughout the 20th century, public policies for women’s health focused care on biological and reproductive dimensions, and birth control technologies. Technoscience advances in producing knowledge and interventions regarding women’s bodies led to a medicalization of labor and birth, consolidating the hospital as an ideal space. This article aims to examine numbers of surgical-cesarean births in the municipality of São Paulo, and to discuss how racial, cultural, social, and economic inequalities influence forms of birth. The statistics have been problematized in their connections with the language of risk, actors, and materialities involved in producing surgical births: public policies for pregnancy, labor, and post-natal care; hospitals. Research was carried out in the repository of public data on births in the municipality of São Paulo, in the period between 2010 and 2016, focusing on types of birth, in relation to place of birth, and women’s race/color and levels of education. The analysis indicated that the majority of births are surgical-cesarean, at a number five times higher than that recommended by the World Health Organization; the number is even higher at private hospitals and among women who declared themselves as White or Asian. Higher levels of education are also linked to this elevated number of births. Vaginal birth numbers were greater in public hospitals for women who declared themselves as Black, Mixed Race, and Native Brazilian. The language of risk guides public policies, delivery practices, and childbirth in Brazil. The lack of investment in birth centers in the country encourages hospitalization. Health professionals attending births have a central role in maintaining the culture of surgical delivery. Surgical-cesarean birth as a woman’s choice is an argument based on childbirth myths, on incorrect information about physiological and psychological processes, and lack of support from health professionals and families faced with the desire for vaginal birth. The complexity of the situation demands recognition that these realities are built on several factors, interconnected in the day-to-day of health services.